Diversidade polínica, caracterização físico-química e perfil voláteis de méis de abelhas sem ferrão de um meliponário urbanode Belterra, Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Meliponiculture, the creation of stingless bees, is a bioeconomic activity practiced in the Amazon, especially by the populations of traditional communities. The activity fits into the concepts of sustainable use of natural resources and therefore considers the ecological importance of the insect/plant interaction as the main pollinating agents. The honey produced by bees from the nectar collected from flowers is the product from the hive most used by humans, either as food or for medicinal purposes. However, the physicochemical composition, quality and sensory characteristicsare influenced by seasonality, botanical origin of the nectar, edaphoclimatic and entomological conditions, harvesting, processing and storage methods. The characterization of honey from stinglessbees from the Lower Amazon, originating from the rational creation of urban meliponaries, is still scarce, therefore, the objective of this study was to know the pollen spectrum, to evaluate if there isa difference in the physical-chemical profile and in the volatile constituents of honey samples from six species of native stingless bees, rationally reared in an urban meliponary in Belterra, Pará, Brazil. To this end, 12 samples of honey from stingless bees were collected directly from the hives using techniques of good manufacturing practices, in two periods: May (rainy period) and October (less rainy period) of 2021. Pollen analyzes of the honeys were carried out , through melissopalynology and physicochemical (acidity index, total ash, pH, humidity and soluble solids, viscosity and HMF).The volatile constituents were analyzed by gas chromatography coupled to mass spectrometry (GC- MS). The results were divided into two chapters, which are presented in the format of a manuscript submitted or to be submitted. In chapter I we evaluated the pollen spectrum of honey samples from different species of stingless bees (Scaptotrigona aff. xanthotricha, Scaptotrigona polysticta, Tetragona clavipes, Tetragonisca angustula, Melipona seminigra, Friseomelitta longipes), where it was observed that the bees collected 90 pollen types in the rainy period (May) and 102 types in the less rainy period (October). The results showed that the pollen diversity observed in the samples varied between bee species and suggest that Tetragona clavipes is the most generalist species while Melipona seminigra has less diversified botanical visitation. In chapter II, the results obtained revealed that the samples of honey from native stingless bee species collected in the urban meliponaryof Belterra, Pará, Brazil were consistent with the parameters indicated by current legislation with regard to pH, total acidity, to the ash content and the amounts of HMF. However, as expected, the moisture content was above that required by current legislation in 11 samples. It is worth mentioningthat even though the harvest was carried out considering the criteria of good manufacturing practices,the moisture content remained high and is an inherent characteristic of honey from stingless bees. The result regarding the electrical conductivity is related to the ash and acidity content, and the viscosity are related to the characteristics of the producing species, handling and environmental characteristics. The profiles of volatile constituents varied between producing species and harvest period, even with hives installed in the same environment.
Keywords: Abelhas indígenas; Características Sensoriais; Meliponicultura; Sazonalidade; CNPQ::CIÊNCIAS BIOLÓGICAS; Bioprospecção e Manejo de Recursos Naturais da Amazônia.